Turnover Intention in Female Workers: The Role of Work-Family Conflict and Work Engagement - Daffa Dwi Sri Diyanti; Andik Matulessy; Rr. Amanda Pasca Rini (Jurnal Psikologi Teori dan Terapan, 2026)
Background: The increasingly advanced industrial development increases the need for labor, but the intention to quit remains a significant challenge because it can harm companies through recruitment costs and the loss of high-quality human resources. This issue is particularly relevant for female workers who often face challenges balancing professional roles with family responsibilities. Objective:  This study aims to determine the relationship between work-family conflict and work engagement with intention to quit among working women in East Java. Method: This study used a quantitative correlational design with a sample of 149 female workers obtained through simple random sampling. Data were collected using scales adapted from the Work-Family Conflict scale, the Utrecht Work Engagement Scale (UWES), and the Intention to Quit Scale, then analyzed using multiple regression analysis. Results:  The results showed that work-family conflict and work engagement together were significantly correlated with intention to quit (F = 7.758; p < 0.01). However, individually, work-family conflict did not correlate with intention to quit (p = 0.290), while work engagement showed a significant correlation with intention to quit (p = 0.001). Conclusion: It is concluded that work engagement is a more dominant factor influencing the intention to quit among female workers compared to work-family conflict, providing an effective contribution of 11.89%. Abstrak Latar Belakang: Perkembangan industri yang semakin maju meningkatkan kebutuhan tenaga kerja, namun niat berhenti kerja tetap menjadi tantangan signifikan karena dapat merugikan perusahaan melalui biaya perekrutan dan hilangnya sumber daya manusia berkualitas tinggi. Masalah ini sangat relevan bagi pekerja perempuan yang sering menghadapi tantangan menyeimbangkan peran profesional dengan tanggung jawab keluarga. Tujuan: Studi ini bertujuan untuk mengetahui hubungan antara konflik kerja-keluarga dan keterlibatan kerja dengan niat berhenti kerja di kalangan perempuan yang bekerja di Jawa Timur. Metode:  Penelitian ini menggunakan desain kuantitatif korelasional dengan sampel 149 pekerja perempuan yang diperoleh melalui pengambilan sampel acak sederhana. Data dikumpulkan menggunakan skala yang diadaptasi dari skala Konflik Kerja-Keluarga, Skala Keterlibatan Kerja Utrecht (UWES), dan Skala Niat Berhenti Kerja, kemudian dianalisis menggunakan analisis regresi berganda. Hasil: Hasil menunjukkan bahwa konflik kerja-keluarga dan keterlibatan kerja bersama-sama berkorelasi signifikan dengan niat berhenti kerja (F = 7,758; p < 0,01). Namun, secara individual, konflik kerja-keluarga tidak berkorelasi dengan niat berhenti kerja (p = 0,290), sedangkan keterlibatan kerja menunjukkan korelasi yang signifikan dengan niat berhenti kerja (p = 0,001). Kesimpulan:  Disimpulkan bahwa keterlibatan kerja merupakan faktor yang lebih dominan yang memengaruhi niat berhenti kerja pada pekerja perempuan dibandingkan dengan konflik kerja-keluarga. Keterikatan kerja memberikan kontribusi efektif sebesar 11,89% terhadap intention turnover pada perempuan yang bekerja.